1993
DOI: 10.1021/bi00212a039
|View full text |Cite
|
Sign up to set email alerts
|

An active-site peptide containing the second essential carboxyl group of dextransucrase from Leuconostoc mesenteroides by chemical modifications

Abstract: The treatment of Leuconostoc mesenteroides B-512F dextransucrase with 10 mM 1-ethyl-3-[3-(dimethylamino)propyl]carbodiimide (EDC) and glycine ethyl ester (GEE) inactivated the enzyme almost completely within 24 min where the modification of one carboxyl group/mol of the enzyme by EDC was attained. Though 30 mM diethyl pyrocarbonate (DEP) also inactivated the enzyme, about 35% of the activity remained during a 36-min incubation. When 10 mol of imidazole residues/mol of the enzyme was modified by DEP, 50% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 33 publications
(40 reference statements)
1
45
0
Order By: Relevance
“…Experimental evidence supports the idea that sites for sucrose cleavage and glucosyl transfer are distinct [2,47]. Thus in an L. mesenteroides dextran sucrase the sequence immediately preceding the predicted H3 has been implicated in sucrose binding and cleavage [12], while in glucosyltransferases the C-terminal region is recognised as a dextranbinding domain and a segment of ca. 300 residues following E3 is necessary for full transferase activity [10,[48][49][50].…”
Section: Relation Between Active Site and Gtf-reactionsmentioning
confidence: 60%
See 1 more Smart Citation
“…Experimental evidence supports the idea that sites for sucrose cleavage and glucosyl transfer are distinct [2,47]. Thus in an L. mesenteroides dextran sucrase the sequence immediately preceding the predicted H3 has been implicated in sucrose binding and cleavage [12], while in glucosyltransferases the C-terminal region is recognised as a dextranbinding domain and a segment of ca. 300 residues following E3 is necessary for full transferase activity [10,[48][49][50].…”
Section: Relation Between Active Site and Gtf-reactionsmentioning
confidence: 60%
“…Information is lacking on their threedimensional structure, but short stretches of sequence similarities exist [10][11][12] between the glucosyltransferases and the aamylases and related amylolytic enzymes that belong to a superfamily of multidomain proteins with a catalytic (fl/c08-barrel domain [13][14][15][16][17][18][19][20][21][22]. These barrel domains contain a few invariant residues involved in the enzyme mechanism and also flstrand-associated sequence motifs which provide a fingerprint of the enzyme origin and specificity [1 623].…”
Section: Introductionmentioning
confidence: 99%
“…Primary sequence alignment revealed that this nanopeptide is highly conserved in the amylases and K-glucosidases [13]. A second active site identi¢ed by Funane et al [14] and by our group [13] that two Asp residues in Gtf-P1 are essential for sucrase activity but may play di¡erent roles in GtfB and -C [15]. Taken together, the N-terminal one-third of the GTFs may play a central role in sucrose splitting and glucan synthesis.…”
Section: Introductionmentioning
confidence: 86%
“…Glucansucrase activity was assayed colorimetrically by the Nelson-Somogyi procedure 20) by measuring the release of reducing sugar from sucrose with glucose as a standard, as described previously. 21) One unit of dextransucrase releases 1 mole of reducing sugar from sucrose per min. Protein concentration was measured using a BCA protein assay reagent (Pierce) with bovine serum albumin as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…2, ), containing the region ''LLANDVNSNP'' reported in L. mesenteroides. 21,24) The amino acid sequences of Site 1 are conserved in glucansucrases with about 50 to 70% identity, but there are no significant similar amino acid sequences in other proteins even in closely related family 13 enzymes. The identity of amino acid sequence of Site 1 of DSRS and DSRT5 is 55%.…”
Section: Preparation Of Glucansucrase Chimeric Enzymesmentioning
confidence: 99%